Longitudinal Course of Illness in Congenitally Deaf Patient with Auditory Verbal Hallucination - Yoshihiro Matsumoto; Nobutaka Ayani; Yurinosuke Kitabayashi; Jin Narumoto (Case Reports in Psychiatry)
Auditory verbal hallucination is one of the core symptoms of schizophrenia, same as delusions, and also occurs in many other psychiatric disorders. Significant numbers of people with congenital deafness experience auditory verbal hallucinations; however, there are only a few reports regarding the course of psychosis in people with congenital deafness. Herein, we report the case of a patient with congenital deafness and auditory verbal hallucinations whose diagnosis was changed from psychotic major depression to schizophrenia 7 years after the onset of the disease. His psychotic symptoms decreased when his primary medication was changed from an antidepressant to antipsychotic drugs, based on the change of diagnosis. In the treatment of congenitally deaf patients with auditory verbal hallucinations, the inability to communicate through spoken language may interfere with proper diagnosis and treatment. The ability to collect detailed information in ways other than through verbal language is imperative for psychiatrists to determine the appropriate diagnosis and treatment for these patients during the longitudinal course of illness.